Al-Taṣawwuf wa al-Ṭuruq al-Ṣūfiyyah fī Indūnīsiyā - Hamid Nasuhi Zain (Studia Islamika, 1996)
Since the 17th century, the history of tasawwuf or mysticism and Islamic congregation in Indonesia shows the dynamics and development. At that time, the world is very fierce battle marked tasawwuf among which tends unortodoks (wujudiyyah) with the orthodox (fiqh orientation). This phenomenon can be seen both in Java and in Aceh. Pendulum understand Sufism in Aceh during the first swing to flow wujudiyyah pioneered Fansuri Hamzah and his teachings later developed by his student, Shams al-Sumatrani. This paper discusses the history and development of tasawwuf and Sufi congregations in Indonesia dates to the 17th century until the early 20th century.DOI: 10.15408/sdi.v3i3.803